2013
DOI: 10.1371/journal.pone.0079768
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the CXCL12/CXCR4-Axis as Preventive Therapy for Radiation-Induced Pulmonary Fibrosis

Abstract: BackgroundA devastating late injury caused by radiation is pulmonary fibrosis. This risk may limit the volume of irradiation and compromise potentially curative therapy. Therefore, development of a therapy to prevent this toxicity can be of great benefit for this patient population. Activation of the chemokine receptor CXCR4 by its ligand stromal cell-derived factor 1 (SDF-1/CXCL12) may be important in the development of radiation-induced pulmonary fibrosis. Here, we tested whether MSX-122, a novel small molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 19 publications
0
57
1
Order By: Relevance
“…Robust upregulation in serum and BAL CXCL12 levels following injury highlighted that the CXCR4/CXCL12 axis mediates MSC recruitment. Contrary to the previous study, inhibition of MSC recruitment with a CXCR4 antagonist attenuated radiation-induced fibrosis (Shu et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurycontrasting
confidence: 86%
See 1 more Smart Citation
“…Robust upregulation in serum and BAL CXCL12 levels following injury highlighted that the CXCR4/CXCL12 axis mediates MSC recruitment. Contrary to the previous study, inhibition of MSC recruitment with a CXCR4 antagonist attenuated radiation-induced fibrosis (Shu et al, 2013).…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurycontrasting
confidence: 86%
“…Whether bone marrow (BM) MSCs circulate in humans has been the subject of debate (Hoogduijn et al, 2014;Mansilla et al, 2006;Wang et al, 2006). Despite this, recent studies conducted in animal models of injury have provided robust evidence that endogenous bone marrow-derived stromal cells can circulate and localise in injured tissue (Chen et al, 2010;Gao et al, 2014;Hong et al, 2009;Shu et al, 2013). In a study by Gao et al, endogenous Nestin+ MSCs were recruited to the lungs of Nes-GFP-transgenic mice challenged intranasally with cockroach allergen.…”
Section: Mechanisms Of Msc and Pericyte Recruitment To Sites Of Injurymentioning
confidence: 99%
“…It has been reported that the activation of the CXCL12/CXCR4 axis was important in the development of radiation-induced pulmonary fibrosis (14). The CXCL12/CXCR4 axis participated in the vascularization induced by radiation and was closely associated with the recurrence and metastasis of breast cancer subsequent to radiation.…”
Section: Expression Of the Cxcl12/cxcr4 Axis In Lung Tissues Of Micementioning
confidence: 99%
“…It has previously been reported that activation of the chemotactic receptor CXCR4 by the ligand CXCL12 was important in the development of radiation-induced pulmonary fibrosis (14). Subsequent to radiation-induced injury, bone marrow-derived fibroblast progenitor cells, also termed fibrocytes, which express CXCR4, are recruited to regions of fibrosis in the lung (25,31).…”
Section: A B Cmentioning
confidence: 99%
“…Several small molecule CXCR4 antagonists (e.g. AMD3100, MSX-122, TN14003) have been developed and some of them significantly reduced bleomycin or radiation-induced pulmonary fibrosis in mice 48,[73][74][75] . Plerixafor (solution of AMD3100 for subcutaneous injection, brand name: Mozobil™, Genzyme Corporation) has been approved by the United States Food and Drug Administration (FDA) and European Medicines Agency (EMA) for use in hematopoietic stem cells (HSC) mobilization for autologous transplant for patients with non-Hodgkin's lymphoma and multiple myeloma (MM) 76 .…”
Section: Potential Therapy Targeted On Circulating Fibrocyte and Cxcr4mentioning
confidence: 99%